Diffrent Social Structures in Istanbul Coasts and Relaitions with the Coasts - Dikcinar Sel, Berna (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2018)
Istanbul has a privileged place among the settlements established around the world in terms of its geographical features. However, immigration from the rural to the city and the rapid urbanization that has taken place have changed the relationship that Istanbul has established with water. Based on this change, the article examines the social, cultural and economic structure of the residents of Istanbul coastal settlements as of 2011. In this review, household surveys conducted in the Black Sea and Marmara coasts of European and Anatolian enclaves and settlements on two coasts of the Bosphorus are used and the findings are defined as spatial. Household surveys were evaluated in two categories; 1) Socioeconomic structure: identification of the general profile and demographic components of households. 2) Use of coastal areas: determination of the nature of coastal areas, relationships between user and existing functions. As a result of the evaluation, the following questions were tried to be answered; 1. The coastal regions where the population with different socio-economic structure shows concentration, 2. The population with different socio-economic structure, the coastal area, the coastal use and the coastal perception, 3. Basic characteristics of the physical environment of the coastal areas where the population with different socio-economic structure concentrates. Although the population living in coastal regions of Istanbul has different characteristics in terms of socio-economical results, it is seen that coastal and coastal relations do not vary much, and that the coastal area of the city has a very weak relation with the coastal area and the perception and expectations related to coastal areas are low.
Keywords: Urbanization; coast; perception of the coast; social structure; Architecture